2010
DOI: 10.1007/s11113-010-9185-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Institutional Constraints: An Analysis of Parental Leave Use and Duration in Spain

Abstract: Parental leave, Work–family balance, Gender equality, Simultaneous equations, Spain,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 30 publications
9
97
0
13
Order By: Relevance
“…Earlier studies have shown that the present system of leave favours re-conciliation essentially among people better positioned on the labour market (Lapuerta et al 2011 ) For that reason, it is anticipated that the present Spanish context, characterised by high unemployment (around 25 %), deteriorating working conditions and high job uncertainty (García and Ruesga 2014 ;Alonso and Fernández Rodríguez 2013 ), discourages leave-taking. From a microeconomic perspective, while the equation is not simple, the couple's job situation is a determinant: men would be expected to act according to cost/benefi t logic to maximise their position on the labour market (in terms of salary and stability).…”
Section: Factors Encouraging Men To Take Leave Alonementioning
confidence: 99%
“…Earlier studies have shown that the present system of leave favours re-conciliation essentially among people better positioned on the labour market (Lapuerta et al 2011 ) For that reason, it is anticipated that the present Spanish context, characterised by high unemployment (around 25 %), deteriorating working conditions and high job uncertainty (García and Ruesga 2014 ;Alonso and Fernández Rodríguez 2013 ), discourages leave-taking. From a microeconomic perspective, while the equation is not simple, the couple's job situation is a determinant: men would be expected to act according to cost/benefi t logic to maximise their position on the labour market (in terms of salary and stability).…”
Section: Factors Encouraging Men To Take Leave Alonementioning
confidence: 99%
“…Parental leave allows the parents to leave the labor market for three years without economic compensation (only certain regions offer compensation, but it is not a substitute for wages). Although it is diffi cult to obtain a reliable indicator, existing data shows that less than 3% of mothers and only 0.1% of fathers ask for this leave for any period of time, and those who do are primarily women with high education levels and stable employment (Lapuerta et al, 2011). Reducing the work day to take care of children is also a measure that is used primarily by women, although we lack adequate data to know the number of persons using this measure and how much their working hours are reduced.…”
Section: The Spanish Casementioning
confidence: 99%
“…El permiso para cuidado de los hijos permite a los padres y a las madres salir del mercado laboral durante tres años sin compensación económica (solo algunas comunidades ofrecen compensaciones, pero estas no sustituyen el salario). Aunque es difícil obtener un indicador fi able, los datos existentes apuntan a que menos del 3% de las madres y solo un 0,1% de los padres solicitan este permiso durante algún tiempo, y que se trata sobre todo de mujeres con altos niveles educativos y con estabilidad en sus empleos (Lapuerta et al, 2011). La reducción de jornada para el cuidado de hijos también es una medida utilizada sobre todo por mujeres, aunque carecemos de datos adecuados para conocer el número de reducciones y la proporción de trabajo reducido.…”
unclassified
“…Since parental leave is unpaid, however, only about 3 percent of eligible mothers and 0.1 percent of eligible fathers make use of it, making parental leave of little practical relevance (Lapuerta et al 2011). In order to claim leave rights, a worker must have made a minimum amount of contributions into social security, which is normally set at 180 days during the seven years immediately before beginning leave or 360 days during the mother's or father's entire working career (Ministerio de Empleo y Seguridad Social 2014).…”
Section: Short Maternity/paternity Leavementioning
confidence: 99%